Amalan tingkah laku beretika kaunselor pelatih - Umi Shamsiah, Abu Bakar (Universiti Malaysia Sarawak, UNIMAS, 2007)
This is a quantitative study to determine practices of trainee counsellors’ ethical behaviour, to determine the difference between demographical factors (gender and ethnic) with ethical practice which are confidentiality, do not exploit, treat people with respect and acting with informed consent. Questionnaires were given to 77 trainee counsellors who are second year and third year students at Counselling Department, University Malaysia Sarawak (UNIMAS). Purposive Sampling method had been choosen in this study. The data was analysed by Statistical Package for Social Sciences (SPSS-windows) 12 version. The result shows that there is no significant difference between demographical factor (gender) with trainee counsellors’ ethical behaviour in confidentiality. There are however difference between demographical factor (gender) with trainee counsellors’ ethical behaviour by do not exploit, treating people with respect and acting with informed consent. The result shows that there is no significant difference between demographical factor (ethnic) with trainee counsellors’ ethical behaviour in confidentiality, do not exploit, treat people with respect for their dignity and acting with informed consent.